Advancement in polymer therapeutics and characterization - Shah, Pratik A; Shelat, Pragna; Dave, Divyang; Shah, Gaurang (Asian Journal of Pharmaceutics (AJP), 2014)
The beauty of the discipline, polymers in drug delivery, is its longevity and self-transforming quality. Polymers have, for decades, performed a valuable function as excipients in tablet and capsule formulations, moving steadily into the parenteral arena as blood circulation time enhancers, and are now capable of offering advanced and sophisticated functions (such as drug targeting) to medicine. Polymers have unique cooperative properties that are not found with low-molecular weight compounds and therein lies the root of their success. Polymers are used as carriers for the delivery of drugs, proteins, targeting moieties, and imaging agents. Several polymers, polyethylene glycol, N-(2-hydroxypropyl) methacrylamide, and polylactide-co-glycolidecopolymers have been successfully utilized in clinical research. Recently, interest in polymer conjugation with biologically active components has increased remarkably as such conjugates are preferably accumulated in solid tumors and can reduce systemic toxicity. Further, it is essential to elucidate the structure–activity relationshipof a drug when it is conjugated with a polymer using different conjugation sites as this can vary the efficacy and mechanism of action when compared with its free form.This review will discuss the current advancement in drug targeting with polymers, smart polymers and recombinant polymers for drug delivery. Finally, it will also highlight on various methods of polymer characterization, including various techniques for polymer molecular weight measurement.